2019
DOI: 10.1126/scitranslmed.aau4760
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis and prolongevity signaling in young germ-free mice transplanted with the gut microbiota of old mice

Abstract: The gut microbiota evolves as the host ages, yet the effects of these microbial changes on host physiology and energy homeostasis are poorly understood. To investigate these potential effects, we transplanted the gut microbiota of old or young mice into young germ-free recipient mice. Both groups showed similar weight gain and skeletal muscle mass, but germ-free mice receiving a gut microbiota transplant from old donor mice unexpectedly showed increased neurogenesis in the hippocampus of the brain and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
154
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(161 citation statements)
references
References 56 publications
2
154
1
4
Order By: Relevance
“…A recent report demonstrated the involvement of the intestinal microflora in maturation and function of microglial cells in the CNS through SCFA signaling pathway in the brain (Erny et al, 2015). Moreover, sodium butyrate enhanced hippocampal neurogenesis in germ-free mice (Kundu et al, 2019).…”
Section: Gut Microbiota-brain Axis and The Potential Influence Of Micmentioning
confidence: 98%
“…A recent report demonstrated the involvement of the intestinal microflora in maturation and function of microglial cells in the CNS through SCFA signaling pathway in the brain (Erny et al, 2015). Moreover, sodium butyrate enhanced hippocampal neurogenesis in germ-free mice (Kundu et al, 2019).…”
Section: Gut Microbiota-brain Axis and The Potential Influence Of Micmentioning
confidence: 98%
“…Thus, it is plausible to hypothesize that age-associated changes in the microbiota composition have a direct effect on the CNS, potentially contributing to the decline of cognitive function seen in the elderly. Recently, it has been reported that FMT from aged donor mice into young germ-free (GF) recipients increased hippocampal neurogenesis, intestinal growth, and activation of the prolongevity signaling pathways in the liver [16]; however, up to date the direct impact of the ageing microbiota on cognitive functioning and activity has not been addressed. We report that FMT from aged mice led to a decline of spatial learning and memory in young adult (henceforth termed adult) recipients via modulation of synaptic plasticity-and neurotransmission-related proteins in the hippocampus, an area of the CNS known to be heavily affected by the ageing process [17].…”
Section: Introductionmentioning
confidence: 99%
“…В одной из последних статей P. Kundu и соавт. [8] приведены результаты экспериментального исследования, где убедительно доказана тесная связь между микробиотой кишечника и возрастными изменениями мозга. В этой работе исследователи пересадили кишечную микробиоту от старых мышей к молодым, что способствовало росту новых нейронов в области гиппокампа наряду с увеличением общей площади поверхности кишечника у реципиентов.…”
Section: связь микробиота-кишечник-мозгunclassified
“…Обнаруженный факт стимуляции роста новых нейронов теоретически можно было связать с действием мозгового нейротрофического фактора BDNF, терапевтический потенциал которого при повреждении головного мозга достаточно хорошо известен [10]. Действительно, в поиске возможных причин активации нейрогенеза у мышей под влиянием «молодой» микробиоты исследователи обнаружили повышенный уровень BDNF, причем было показано, что активация этого белка происходила под влиянием бутирата -одной из короткоцепочечных жирных кислот ключевого микробного метаболита через увеличение уровня фактора роста фибробластов 21 (FGF21) -сигнального антивозрастного белка [8].…”
Section: связь микробиота-кишечник-мозгunclassified